Antibacterial and anti-inflammatory activities of marine Brevibacterium sp. - Vennam Srilekha; Gudikandula Krishna; Vutukuru Seshasrinivas; Maringanti Alha Singara Charya (Wolters Kluwer Medknow Publications, 2017)
The marine environment covers three quarters of the surface of the planet and is estimated to be home to more than 80% of life but yet it remains largely unexplored. It harbours a number of macro and microorganisms that have developed unique metabolic abilities to ensure their survival in diverse and hostile habitats, resulting in the biosynthesis of an array of secondary metabolites with specific activities. In this study, pigment forming bacterial strains were isolated from the sea surface inter tidal zones at different sampling sites along the Visakhapatnam coastal region. The bacterial isolates showed various types of colour pigments like pink, yellow, orange, and brown. Out of 26 pigmented isolates obtained, the bacterial isolate with bright yellow pigmentation was selected for further study. This strain was identified as Brevibacterium sp by using morphological, physiological, biochemical and 16s rRNA sequencing methods. The pigment was extracted in methanol solvent and antibacterial activity of the pigments extracted from the bacteria was determined and it was found active against pathogenic bacteria. The pigment extract was tested In vivo for anti-inflammatory activity and was effective.